Pharmacologic neuroprotective agents for the treatment of perinatal asphyxia in low-income and lower-middle-income countries: A systematic review and meta-analysis of randomised controlled trials - Victor Ayodeji Ayeni; Aisha Adam Abdullahi; Abdulmuminu Isah; Love Bukola Ayamolowo; Timothy Adeyemi; Motunrayo Adebukunola Oladimeji; Ufuoma Shalom Ahwinahwi; Vitalis Ikenna Chukwuike; Oluchukwu Perpetual Okeke; Olunike Rebecca Abodunrin; Folahanmi Tomiwa Akinsolu; Olajide Odunayo Sobande (PLoS ONE, 2025)
Background Perinatal asphyxia (PA) is a major contributor to neonatal mortality and long-term neurodevelopmental impairment, particularly in low- and middle-income countries (LMICs), where the effectiveness of therapeutic hypothermia remains limited. Pharmacologic neuroprotective agents have shown potential as alternative treatments, but their efficacy in low-income and lower-middle-income countries (LILMICs) is not well established. This systematic review aimed to assess the effectiveness of pharmacologic interventions in neonates with PA in LILMICs. Methods A systematic search of PubMed, Web of Science, CINAHL, and Google Scholar was conducted for randomised controlled trials (RCTs) published between 2000 and 2024. Eligible studies compared pharmacologic neuroprotective agents with placebo or standard care, excluding therapeutic hypothermia, among neonates diagnosed with PA in LILMICs. Data on survival and neurodevelopmental outcomes were extracted and synthesized; meta-analyses were conducted where appropriate. Results Twelve RCTs involving 1,008 neonates were included. The majority (91.7%) of studies were conducted in Asia, with only one study from Africa. Magnesium sulphate was the most frequently evaluated agent (66.7% of studies), followed by melatonin, topiramate, erythropoietin, and citicoline. Melatonin was associated with improved survival, and all agents showed improved short-term neurological outcomes. Neurodevelopmental outcomes at 3, 6, 12, and 19 months were generally favourable, though data remained limited. Conclusion Pharmacologic neuroprotective agents show promise in improving survival and neurological outcomes in neonates with PA in LILMICs. However, more robust, multi-center RCTs are needed to confirm their efficacy and establish them as feasible alternatives to therapeutic hypothermia in these settings.